2016
DOI: 10.1111/vco.12280
|View full text |Cite
|
Sign up to set email alerts
|

High COX‐2 expression in canine mast cell tumours is associated with proliferation, angiogenesis and decreased overall survival

Abstract: COX-2 overexpression is associated with several hallmarks of carcinogenesis such as proliferation, angiogenesis, invasion and metastasis. Fifty cases of canine mast cell tumours (MCT) were retrospectively evaluated and submitted to immunohistochemistry for COX-2, CD31, Ki-67, MAC-387 and CD3. Furthermore its relationship with clinicopathological variables and overall survival (OS) was analysed. COX-2 intensity (P = 0.016), but not COX-2 extension nor score was associated with decreased OS and higher grades of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Furthermore, known correlations between lymphocyte phenotypes and specific functions have been used to elucidate other prognostically significant lymphocyte subsets such as Th1, Th2, Th17, γ/δ‐T cells, CD8 + CD103 + T cells, and lymphocyte memory subsets, in addition to prognostic markers of T cell exhaustion, in a variety of human tumours . Indeed, the variability of CD3+ infiltrates in predicting prognosis in certain canine tumour types may be explained by the heterogeneity of TILs function that exists, emphasizing the need for more detailed phenotypic analyses of lymphocyte subsets in future studies …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, known correlations between lymphocyte phenotypes and specific functions have been used to elucidate other prognostically significant lymphocyte subsets such as Th1, Th2, Th17, γ/δ‐T cells, CD8 + CD103 + T cells, and lymphocyte memory subsets, in addition to prognostic markers of T cell exhaustion, in a variety of human tumours . Indeed, the variability of CD3+ infiltrates in predicting prognosis in certain canine tumour types may be explained by the heterogeneity of TILs function that exists, emphasizing the need for more detailed phenotypic analyses of lymphocyte subsets in future studies …”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed the relationship of COX-2 overexpression with shorter OS and/or PFS (62, 66), however in others no such relationship was found (32). Contradictory data concerning any connection between increased COX-2 expression and a bad prognosis, shorter OS and a worse response to treatment were also obtained in the studies of some tumours in dogs and cats (11, 37, 80).…”
Section: Clinical Significance Of Cox-2 Expressionmentioning
confidence: 96%
“…However, neither system predicts metastasis. It worth to note that COX-2 overexpression is associated with decreased overall survival and higher grades of malignancy according to Patnaik and Kiupel grading systems [46].…”
Section: Mast Cell Tumorsmentioning
confidence: 99%